Genetic structure and forensic characteristics of Tibeto-Burman-speaking Ü-Tsang and Kham Tibetan Highlanders revealed by 27 Y-chromosomal STRs - He, Guanglin; Wang, Zheng; Su, Yongdong; Zou, Xing; Wang, Mengge; Chen, Xu; Gao, Bo; Liu, Jing; Wang, Shouyu; Hou, Yiping (Scientific reports, 2019)
Culturally diverse Tibetans (Ü-Tsang, Kham and Ando) harboring a unique molecular mechanism that allows them to successfully adapt to hypoxic environments in the Qinghai-Tibet Plateau have been a subject of great interest in medical genetics, linguistics, archeology and forensic science. However, forensic characteristics and genetic variations of the Y-chromosomal 27-marker haplotype included in the Yfiler Plus system in the Ü-Tsang and Kham Tibeto-Burman-speaking Tibetans remain unexplored. Thus, we genotyped 27 Y-STRs in 230 Shigatse Ü-Tsang Tibetans (SUT) and 172 Chamdo Kham Tibetans (CKT) to investigate the forensic characterization and genetic affinity of Chinese Tibetan Highlanders. The haplotype diversities were 0.999962028 in SUT and 0.999796002 in CKT. Forensic diversity measures indicated that this 27-Y-STR amplification system is appropriate for routine forensic applications, such as identifying and separating unrelated males in deficiency paternity cases, male disaster victims and missing person identification and determining male components in sexual assault cases. Moreover, the genetic relationships among 63 worldwide populations (16,282 individuals), 16 Asian populations, and 21 Chinese populations were analyzed and reconstructed using principal component analysis, multidimensional scaling plots and a phylogenetic tree. Considerable genetic differences were observed between Tibetan populations and other geographically/ethnically diverse populations (Han Chinese). Our studied SUT and CKT have a genetically closer relationship with Gansu Ando Tibetans than with other Asians. In total, our analyses indicated that subpopulation structures exist among Asian and Chinese populations, and population-specific reference databases should be established for forensic applications.